Pengaruh Kedisiplinan Belajar Terhadap Hasil Belajar Matematika Peserta Didik Kelas V Sekolah Dasar - Shinta, Dewi; Riyadi, Riyadi; Atmojo, Idam Ragil Widianto (Universitas Sebelas Maret, 2023)
This riset aims to determine whether there is a positive effect of learning discipline on the cognitive learning outcomes of mathematics for fifth grade students of public elementary schools in Laweyan sub-district. The quantitative methodologies used in this study are survey-type with an associatie research design. Students in fifth grade from elementary school in Laweyan Subdistrict made up the entire study’s population in the 2022/2023 academic year. The research sample was fifth grade students at SD N Pajang IV, SD N Tunggulsari 01, SD N Bratan 02 with a total of 71 students. Tests and questionnaires have been used as the data collection methods. Simple linear regression was used to examine the research data. As shown by the acquisition of (19.509) > in the regression equation = 6.078 + 0.869X, the reset’s findings show that learning discipline has a positive and significant impact on the mathematics learning outcomes of fifth grade students in public elementary schools in Laweyan District in the 2022/2023 academic year. According to the analysis of R squared coefficient f determination (0,847), 84,7% of fifth grade children in the public elementary schools in the Laweyan District showed improved math learning outcomes as a result of learning discipline.